Components In Downstream Health Promotions To Reduce Sugar Intake Among Adults: A Systematic Review - Syathirah Hanim Binti Azhar Hilmy; Norhasnida Nordin; Mohd Yusmiaidil Putera Mohd Yusof; Tuan Yuswana Tuan Soh; Norashikin Yusof (BioMed Central Ltd part of Springer Nature., 2024)
Indexed by WOS/Scopus/ERA